A viabilidade financeira do fundo de financiamento ao estudante de ensino superior: FIES para instituição privada - Monteiro, Afonso Celso (2013)
This study aimed to research the FIES Fund Student Financing of Higher Education and its viability within an IES - private Higher Education Institution in the case of this research is an institution of the Paraíba Valley in the city of São José dos Campos - SP. Given an adequate service and hosting by IES through CPSA - Permanent Commission for Supervision and Monitoring, the system user FIES, due to one of the duties of the Institution of IES Vale do Paraíba, to keep the student entered the program FIES, as student regularly enrolled even failing for reasons unrelated to the services of its structure, the delay or lack of transfers from ENDF - National Fund for Education Development, operator of the entire system. The transfers mentioned herein are not in cash but in Treasury Financial Certificates - series E, and that the IES uses for social security payments, or you can sell the surplus to the CEF. The problem is that this work brings a private affair, because it is maintained by a private university Maintainer, the new sponsor this board wants to know if the FIES has viability in the institution if the financial benefits are sufficient, as if they were students paying normal for the HEI, or if the burden is greater, which reaches not compensate the government for the student. Making a scientific sampling, collecting data sector of Scholarships and FIES also responsible for the institution of the Paraíba Valley. Following a group of students who have contracted the FIES in the first half of 2010, only Urbanova Campus, the largest of this institution of the Paraíba Valley. As a result of the research of observation, classification and analysis of collected data, we obtained the following results: From a group of 71 (seventy one) students, only 11 (eleven) students are on indefinite situation and hitherto borne by the institution of Vale do Paraíba, treating them as paying students hypothetically, would not get the "default" to 15% (fifteen percent), index acquitted by the institution. An institution that strives for a sense of community, and serving students in your community then the results end up making the proportionality and sample surveyed FIES program viable in this institution of the Paraíba Valley.